Rapid endogenic rock recycling in magmatic arcs - Jun-Yong Li (Nature Portfolio, 2021)
A case study of migmatites indicates that the juvenile arc crust underwent a rapid self-recycling process from arc magmatism to erosion and weathering at the surface, then to burial and remelting. Intra-arc thrust fault systems might efficiently promote endogenous recycling.